The effect of soft ironcore lamination removal towards cogging torque in an electric generator - Razali, Akhtar Razul (2018)
The generator that normally used in the market, which is the iron-cored electricity generator has high cogging and starting torques. By redesigning of the iron-cored electricity generator, Axial-flux Permanent Magnet (AFPM) configuration minimizes the usage of ferrite material. AFPM, one of the coreless electricity generator configuration has a less counter electromotive force (CEMF) compare to the cored electricity generator. AFPM configuration also has no cogging torque and low starting torque. Application of a coreless electricity generator is the most suitable compare to the cored electricity generator. However, it is expected that the elimination of the ferrite material within the coreless electricity generator itself increases the power generation. The configuration is the ironless electricity generator. This thesis presents the analysis of the AFPM ironless electricity generator. There are two main testing present in this thesis, open circuit test and close circuit test. The result of the analysis shows that the rotational speed proportionally with voltage output for open circuit test. The close circuit test shown power proportionally with rotational speed.